A Brief Introduction to Jainism and Sikhism - Partridge, Christopher (Brief Introductions to World Religions., 2019)
This brief introduction to Jainism and Sikhism is designed to help readers understand these important religious traditions. Known and valued for its balanced approach, this text provides broad coverage of Jainism and Sikhism through an arresting layout. The user-friendly content is enhanced by charts of religious festivals, historic timelines, updated maps, and a useful glossary. It is ideal for courses on South Asian religions and will be a useful reference for all readers eager to learn more.